Chinese language teachers’ dichotomous identities when teaching ingroup and outgroup students - Chen, Haijiao; Sun, Wanting; Han, Jinghe; Liu, Qiaoyun (Frontiers in Psychology, 2022)
Research into second language teacher identity has experienced a shift in recent years from a cognitive perspective to social constructionist orientation. The existing research in Chinese language literature in relation to Foreign Language (CFL) teachers’ identity shift is principally in relation to the change of social, cultural, and institutional contexts. Built on the current literature, this research asks: “How might teachers’ self-images or self-conceptualizations be renegotiated when they are located within their own mainstream cultural and educational system, yet comprised of students from various cultural backgrounds?” The data were collected from a group of CFL teachers in a South China university. The research found that students’ backgrounds largely impacted on, and led to, the teachers’ dichotomous relational identities, but did not dramatically change the teachers’ perception on what or how much subject knowledge to be possessed to make an ideal CFL teacher. This attribute of their identity was sustained even though the teaching content was modified at a practical level in response to groups’ differences. Further, the CFL teachers’ pedagogical identity remained stable with only minor modifications when teaching “ingroups” and “outgroups” of students.